Desain dan Analisis Struktur Bangunan Adat Sumatera Barat Terhadap Ketahanan Gempa - Khairat Mantani; Muhammad Fauzan (Departemen Teknik Sipil dan Lingkungan, IPB University, 2019)
Indonesia is an archipelago with a high risk of earthquakes. Traditional houses in Indonesia are very varied, distinctive, and made of wood. Rumah gadang is one of the traditional houses and located in Minangkabau, West Sumatra. Rumah gadang in various regions are threatened due to natural disasters. The purpose of this research were design and analyze rumah gadang structures againts the durability on earthquake. The analysis used software SAP2000 v14 and Microsoft Excel. The main material was pheasant wood or senna siamea with density 800 kg/m3 and the modulus of elasticity 11000 MPa. Based on the calculation of maximum internal force, the combination of load and resistance factor design (LRFD) was greater than the combination of allowable stress design (ASD). The actual pressure was smaller than the ultimate pressure so structure was fulfill the strength standard. Buckling didn't occur when the ultimate pressure work. Maximum flex occur on the roof was 1.08 cm due to the hight of roof cross-section is smaller than the width off cross-section. Keywords: ASD, earthquake, LRFD, rumah gadang